Implementation of an automated process for Limnospira indica harvesting and culture medium recycling for space applications - Tallec, Jordan; Vandermies, Marie; Coene, Céline; Lamaze-Lefebvre, Brigitte; Demey, Dries; Frappart, Matthieu; Couallier, Estelle (Frontiers in Astronomy and Space Sciences, 2023)
Future long-term space exploration missions require the implementation of circular life support systems for the supply of water, oxygen and food from mission wastes. Therefore, separation systems dealing with multi-phasic streams need to be addressed. The BioHarvest (BHV) study focused on solid/liquid separation in space with the aim to demonstrate the continuous separation and harvesting of the cyanobacterium Limnospira indica from its culture broth under axenic conditions. The cyanobacterium biomass is intended to be used for further food processing while the broth free of organic matter and resupplied with nutrients should be directly recycled into the photobioreactor (PBR). In this study, an automated breadboard model based on a two-step process was built. First, a Biomass Harvesting Unit (BHU) separates the biomass produced in the PBR from the culture medium with dead-end filtration. Second, the Medium Filtration Unit (MFU) further treats the culture medium to retain the dissolved organic compounds using crossflow filtration. The performances of BHU and MHU met the requirements in batch mode and in short continuous mode: the BHU was able to retain all the biomass and the MFU could retain more than 90% of organic matter while being permeable to nutrients. The productivity of the MFU was also very good, with a high permeation flux allowing treating the targeted 80 L of culture per day. However, continuous operation of the BHV technology could not be achieved in the long term due to biomass accumulation as a sticky cake with a high specific resistance on the BHU filter, despite backwashing cycles and intense vibrations. Future work shall therefore focus on this critical step, to improve process performance by preventing fouling of the filter sheets.